Psychological status on informal carers for stroke survivors at various phases: a cohort study in China - Huang, Neng; Tang, Yidan; Zeng, Peng; Guo, Xingtong; Liu, Zuoyan (Frontiers in Psychiatry, 2023)
Abstract Background: In China, the risk of stroke is higher than that in developed countries such as Europe and America. Informal caregivers play a major role in providing support to stroke survivors. Currently, only limited studies on changes in psychological state of the caregivers at different stages of stroke have been published. Purpose: To investigate the stress and psychological state of informal caregivers of stroke patients in different periods and to explore the factors that affet their states. Methods: Using a cross-sectional survey and the convenience sampling method, 202 informal caregivers of stroke patients in a third-grade first-class hospital in Chengdu were selected. Follow-up was conducted by face-to-face interviews, telephone calls, or home visits on days 3, 2 months, and 1 year after onset.We investigated the basic information about the caregivers, including their anxiety, depression and social support conditions. We analyzed the pressure and psychological conditions of informal caregivers at different stages of stroke and analyzed its influencing factors. The data were displayed by the number and percentage of the cases ; the continuous variables were described by means and standard deviation. In addition, the data were compared by Pearson correlation analysis and logistic regression analysis. Results: (1) Within 3 days after the onset of stroke, the informal caregivers had the highest stress, the most severe anxiety and depression, the heaviest burden, and the lowest score of medical-social support. Over time, the pressure and burden of the caregivers are gradually decreasing, anxiety and depression are increasing, and social support is also increasing. (2) The stress and psychological status of informal stroke caregivers are affected by multiple factors, including the caregiver's age, relationship with the patient, patient's age, and patient's physical conditions. Conclusion: The stress and psychological status of informal caregivers varied in the different stages of stroke, and they were affected by several factors. Medical staff should pay attention to informal caregivers while providing care for patients. Relevant interventions may be developed based on the results to improve the health of informal caregivers and thus to promote the health of patients.